2021
DOI: 10.3390/cancers13092068
|View full text |Cite
|
Sign up to set email alerts
|

MiR-182-5p and miR-375-3p Have Higher Performance Than PSA in Discriminating Prostate Cancer from Benign Prostate Hyperplasia

Abstract: Prostate cancer (PCa) is the most commonly diagnosed neoplasm among men. Since it often resembles benign prostate hyperplasia (BPH), biomarkers with a higher differential value than PSA are required. Epigenetic biomarkers in liquid biopsies, especially miRNA, could address this challenge. The absolute expression of miR-375-3p, miR-182-5p, miR-21-5p, and miR-148a-3p were quantified in blood plasma and seminal plasma of 65 PCa and 58 BPH patients by digital droplet PCR. The sensitivity and specificity of these m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 45 publications
2
11
0
Order By: Relevance
“…Similar findings in cell adhesion, migration, and invasion were observed in other PCa cells studies [ 12 , 14 , 16 , 18 , 44 , 45 ] and in other tumor models [ 32 , 46 , 47 ]. Altogether, these results support the oncomiR function of miR-182-5p in regulating cell proliferation, adhesion, and migration of PCa cells, which largely determines their tumorigenic capacity and the observed unfavorable outcome in PCa clinical cases that present with miR-182-5p overexpression [ 8 , 9 , 10 , 12 , 13 , 14 , 15 , 45 ].…”
Section: Discussionsupporting
confidence: 61%
See 2 more Smart Citations
“…Similar findings in cell adhesion, migration, and invasion were observed in other PCa cells studies [ 12 , 14 , 16 , 18 , 44 , 45 ] and in other tumor models [ 32 , 46 , 47 ]. Altogether, these results support the oncomiR function of miR-182-5p in regulating cell proliferation, adhesion, and migration of PCa cells, which largely determines their tumorigenic capacity and the observed unfavorable outcome in PCa clinical cases that present with miR-182-5p overexpression [ 8 , 9 , 10 , 12 , 13 , 14 , 15 , 45 ].…”
Section: Discussionsupporting
confidence: 61%
“…MiRNAs were shown to be dysregulated in PCa, among them the highly conserved miR-183 family. This family is composed of three members, miR-96, miR-182, and miR-183, mapped at 7q32.2, which up-regulation has been reported in PCa clinical cases [ 7 , 8 ]. MiR-182-5p specifically, has been shown to be overexpressed in PCa tissues [ 8 , 9 , 10 , 11 , 12 ] in association with tumor progression and decrease in survival rates [ 10 , 13 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prostate cancer (PC) with high incidence (>1.1 million new cases each year) and mortality (~300,000 deaths per year) presents a significant global public health burden [ 1 , 2 ]. Established risk factors of PC are age, race and family history of disease [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Alam et al found that MiR-375 regulates cell growth, proliferation, cell migration, and apoptosis by modulating the CTGF-EGFR-PIK3CA-AKT signaling axis in human colorectal cancer cells (18) . Furthermore, several investigations were demonstrated that constitutive expression of miR-375 promotes oncogenicity in the breast (19)(20)(21)(22)(23) , prostate (24)(25)(26)(27) , and lung cancer (28) . In addition, few pieces of literature reported that miR-375 functions as a tumor suppressor (16,(29)(30)(31) .…”
Section: Introductionmentioning
confidence: 99%